Establishing the First Student-Run Clinic to Provide Free Health Care to a South Texas Colonia - Cauba, John Nicholas; Callan, Andrew; Alvarado, Joy; Tapia, Beatriz (Journal of Student-Run Clinics, 2024)
The University of Texas Rio Grande Valley School of Medicine (UTRGVSoM) opened its student-run clinic (SRC) in March 2018 to provide free health care for the residents of Pueblo de Palmas colonia in Hidalgo County. Located along the United States-Mexico border near some of the country’s poorest and most medically underserved communities, UTRGVSoM has the unique opportunity to extend quality primary care to those who otherwise would go without. The physical location of the clinic was determined by a partnership with Proyecto Desarrollo Humano, a nonprofit organization within the Pueblo de Palmas colonia. The free clinic, located in the town’s community center, opens its doors to the public every month on a chosen Saturday. This article hopes to detail the experience of being the first SRC to operate inside a Texas colonia.